Microkinetic Barriers of the Oxygen Evolution on the Oxides of Iridium, Ruthenium and their Binary Mixtures. Issue 20 (29th September 2022) - Geppert, Janis; Röse, Philipp; Pauer, Swantje; Krewer, Ulrike
Abstract: The performance of electrocatalytic water splitting in polymer electrolyte membrane electrolysis is substantially determined by the microkinetic processes of the oxygen evolution reaction (OER). Even highly active catalysts such as the nanoparticulated transition metal oxides IrO2, RuO2 and their mixtures, Irx Ru1−x O2, exhibit overpotentials up to several hundreds of millivolts. The surface of the oxide mixtures Irx Ru1−x O2 is found to consist of actives sites of both Ir and Ru on which the OER mechanism is processed independently and at different overpotentials. By applying microkinetic modelling and parameterization via cyclic voltammograms we show that there is a correlation between performance and the relative Ir content, that can be explained by two different deprotonation steps. These are in particular the formation of the adsorbate species *OOH on rutile RuO2 and *OO on IrO2 . The respective free reaction energies are quantified to 1.44 eV and 1.58 eV, which are the highest values of the process and thus determining the overpotential. The additional finding of adsorbed oxygen *O covering >40 % of the active sites during the OER suggests that subsequent water adsorption is the major performance limiting step. Finally, a synergetic effect between both active sites on the binary transition metal oxides is identified: the respective other metal lowers the potential determining reaction energy on the Ru or Ir active site. This insight into the surface processes on Ir and Ru binary oxides forms the basis for deeper understanding of the active sites for further OER catalyst development. Abstract : Water electrolysis : A microkinetic model is parameterized with cyclic voltammograms and exploited to analyze the surface processes on IrO2, RuO2 and their binary Irx Ru1−x O2 mixtures during oxygen evolution. Potential determining reaction energies are identified for the various catalysts and they reveal a synergetic effect: improvement of the overall electrocatalytic activity on both Ru and Ir active sites.